The Role of Futsal Extracurricular Activities as an to Prevent Juvenile Delinquency in Students - Lanang Aditya; Supriyono Supriyono (Universitas Negeri Semarang, 2026)
Juvenile delinquency remains a significant concern in secondary education, emphasizing the importance of school-based preventive interventions that promote positive adolescent development. Among various extracurricular activities, futsal has the potential to serve as an educational medium that fosters discipline, responsibility, teamwork, leadership, emotional regulation, and other life skills that may reduce adolescents' susceptibility to delinquent behavior. This study aimed to examine the role of extracurricular futsal activities in preventing juvenile delinquency among students at SMK Muhammadiyah 1 Semarang. A quantitative survey design was employed involving 30 students who participated in the school's futsal extracurricular program using a total sampling technique. Data were collected through a validated and reliable 30-item questionnaire based on the Positive Youth Development (PYD) framework. Descriptive statistics were used to summarize the data, while the Shapiro-Wilk test was conducted to assess normality. Since the data were not normally distributed, the relationship between extracurricular futsal participation and juvenile delinquency prevention was analyzed using the Spearman Rank correlation test. The results revealed a strong and statistically significant positive relationship between the two variables (p = 0.785, p < 0.001), indicating that greater participation in structured futsal activities is associated with stronger juvenile delinquency prevention. These findings support the Positive Youth Development and Life Skills Development frameworks, suggesting that extracurricular futsal contributes to character formation, social competence, and positive behavioral development beyond improving physical fitness and technical skills. Therefore, schools are encouraged to strengthen extracurricular sports programs by integrating intentional character education and life skills